Formation of Silica-Lysozyme Composites Through Co-Precipitation and Adsorption - van den Heuvel, Daniela B.; Stawski, Tomasz M.; Tobler, Dominique J.; Wirth, Richard; Peacock, Caroline L.; Benning, Liane G. (Frontiers in Materials, 2018)
Interactions between silica and proteins are crucial for the formation of biosilica and the production of novel functional hybrid materials for a range of industrial applications. The proteins control both precipitation pathway and the properties of the resulting silica–organic composites. Here, we present data on the formation of silica–lysozyme composites through two different synthesis approaches (co-precipitation vs. adsorption) and show that the chemical and structural properties of these composites, when analyzed using a combination of synchrotron-based scattering (total scattering and small-angle X-ray scattering), spectroscopic, electron microscopy, and potentiometric methods vary dramatically. We document that while lysozyme was not incorporated into nor did its presence alter the molecular structure of silica, it strongly enhanced the aggregation of silica particles due to electrostatic and potentially hydrophobic interactions, leading to the formation of composites with characteristics differing from pure silica. The differences increased with increasing lysozyme content for both synthesis approaches. Yet, the absolute changes differ substantially between the two sets of composites, as lysozyme did not just affect aggregation during co-precipitation but also particle growth and likely polymerization during co-precipitation. Our results improve the fundamental understanding of how organic macromolecules interact with dissolved and nanoparticulate silica and how these interactions control the formation pathway of silica–organic composites from sodium silicate solutions, a widely available and cheap starting material.